Volume 3: Materials and Joining 2012
DOI: 10.1115/ipc2012-90345
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Pipe Wall Roughness and Pipe Diameter on the Decompression Wave Speed in Natural Gas Pipelines

Abstract: The shock tube experimental results have shown clearly that the decompression wave was slowed down in a pipe with a rough inner surface relative to that in a smooth pipe under comparable conditions. In the present paper a one-dimensional dynamic simulation model, named EPDECOM, was developed to investigate the effects of pipe wall roughness and pipe diameter on the decompression wave speed. Comparison with experimental results showed that the inclusion of frictional effects led to a better prediction than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These are based entirely on assumptions of one-dimensional homogeneous-equilibrium fluid flow. In these models the effects of friction, heat transfer, and pipe diameter can be considered, which is particularly relevant for smaller diameter and longer pipelines where friction could lead to a range of complex effects on local flow conditions, temperature, and pressure within the pipeline [24,[26][27][28][29]. CFD-based techniques involve discretising the governing partial differential equations of fluid flow.…”
Section: Computational Fluid Dynamics (Cfd) Technique Have Been Develmentioning
confidence: 99%
“…These are based entirely on assumptions of one-dimensional homogeneous-equilibrium fluid flow. In these models the effects of friction, heat transfer, and pipe diameter can be considered, which is particularly relevant for smaller diameter and longer pipelines where friction could lead to a range of complex effects on local flow conditions, temperature, and pressure within the pipeline [24,[26][27][28][29]. CFD-based techniques involve discretising the governing partial differential equations of fluid flow.…”
Section: Computational Fluid Dynamics (Cfd) Technique Have Been Develmentioning
confidence: 99%
“…Various tools have been presented in the literature for simple calculations of the decompression wave speed, still following DNV guidelines [5], such as SNE 32(4) -12/2022 GASDECOM [6], EPDECOM [7] and DECOM [8], which employ the assumption of unidimensional isentropic, homogeneous equilibrium and inviscid formulation of the decompression wave without explicitly solving the fluid transport equations [9]. On the other end of the scale various 1-D/2-D CFD based tools have also been demonstrated where the mass, momentum, and energy balances are explicitly solved [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the high-pressure liquid CO 2 in the pipeline turned into a superheated liquid quickly and then transformed into a gaseous state, forming a gas-liquid two-phase flow. Cosham et al [16] established a shock tube test device, which has a length of 144 m and an ID of 146.36 mm. To measure the transient pressure and temperature drops of the CO 2 fluid in the pipe, 35 high-frequency pressure transducers and 14 T-type thermocouples were installed on the pipe wall along the axis.…”
Section: Introductionmentioning
confidence: 99%